Unsealing behaviour: variation in harbour seal (Phoca vitulina) responses to anthropogenic sound in relation to individual health - Maurer, Nina; Boyi, Joy Ometere; Schick, Luca Aroha; Nachtsheim, Dominik André; Schaffeld, Tobias; Gross, Stephanie; Teilmann, Jonas; Schnitzler, Joseph; Siebert, Ursula (Marine Pollution Bulletin, 2025)
Anthropogenic underwater noise can affect animal behaviour, which in turn is influenced by other intrinsic and extrinsic factors. In this case study, we explored links between behaviour, underwater noise and health on 18 free-ranging harbour seals (Phoca vitulina) in the Elbe estuary and Wadden Sea. Individuals were captured and blood samples were taken to assess the health status through leukograms and molecular biomarkers indicative of stress, sound exposure and immunological status. Seals were fitted with long-term sound and movement tags (DTAGs), recording high-resolution three-dimensional diving behaviour and received sound levels simultaneously. Four behavioural states were identified from the seals' dive data (bottom phase duration, prey capture attempts, bottom phase stroke frequency, post-dive duration, descent velocity) using a Hidden Markov Model, and state transitions were linked to received 2 kHz decidecade levels as vessel noise proxy. State transition probabilities varied, but with increasing noise, bottom resting probability decreased, and transit behaviour likelihood increased. Seals remaining in the Elbe were exposed to vessels regularly and showed higher tolerance to underwater noise exposure than seals exposed to fewer vessels. Immunological health parameters (here white blood cells count) also affected the onset of noise-induced state transitions, highlighting the importance of considering health status in behavioural response studies.